MAMPUKAH BADAN USAHA MILIK DESA MENERAPKAN KEADILAN PROSEDURAL? - Marryella Violetha Patiran; Intiyas Utami (Ultima Accounting : Jurnal Ilmu Akuntansi, 2020)
Abstract- The objective of this research to explore the ability of Village-owned enterprise in realizing procedural justice. Village-Owned Enterprises should be able to provide justice for its members, but whether they are able to provide procedural justice to stakeholders, namely administrators and village communities. Research on Village-Owned Enterprises is mostly carried out in terms of governance in general, whereas specifically procedural justice has the potential to be investigated as part of governance implementation. This research was conducted with a qualitative method that traced the facts of procedural justice in the Karya Lestari Manunggal Village Company in Boyolali District. Data in the form of interviews with resource persons, namely the management of the Village Owned Enterprises and community representatives. The results of this study indicate that procedural justice cannot yet be fully realized in the Kalem Village-Owned Enterprises due to limited human resources. Conditions of procedural justice that can be realized in terms of the delivery of information in the Village Development Planning Consultation have been carried out. Procedural justice in village-owned enterprises still needs to be optimized by increasing the capacity of human resources. The Office of Community Empowerment in Boyolali District can provide more intensive training to improve human resources. Keywords: Village-Owned Enterprises, Procedural Justice